Context Matters: Enhancing SoTL by Exploring Interpersonal Relationship Building in Higher Education - Rahman, Nira; Cobb, Hannah; Giddings, Lindsay; Truglia , Mary Helen; Dolan, Sara; Jhangiani, Surita; O'Connor , Kevin (Teaching and Learning Inquiry, 2025)
This paper contributes to SoTL by critically examining the literature on the nature of interpersonal relationships across global higher education settings through narrative inquiry, focusing on both online and in-person learning. Drawing on previous literature (to show patterns of inquiry) and fictional student cases (to give concrete details and examples), this paper examines how educators’ relationships with students shape learning outcomes and experiences and looks at the intricate role of trust in fostering interpersonal relationships within educational settings. The impact of trust is examined across various dimensions—from student-teacher dynamics to peer interactions and institutional structures. Key themes of deliberate interaction, clear communication, and activities for belonging emerge as crucial for fostering supportive learning environments. The analysis underscores the significance of empathetic communication and culturally responsive pedagogies in enhancing student engagement and well-being. Trust, foundational to all those themes, is analyzed through lenses of honesty and benevolence, two essential perspectives for establishing reliable educational environments for students from a variety of societal and educational backgrounds. Through the fictionalized cases, the authors investigate how trust, as cultivated through reflective practices such as the 5Rs framework (Bain et al. 2002), enhances student engagement and inclusivity. By integrating personal reflections and scholarly literature from SoTL, this paper advocates for pedagogical practices that prioritize inclusive, relational approaches in education across diverse contexts.